Cognitive behavioural therapy for thought disorder in psychosis. Issue 4 (2nd October 2017) - Palmier-Claus, Jasper; Griffiths, Robert; Murphy, Elizabeth; Parker, Sophie; Longden, Eleanor; Bowe, Samantha; Steele, Ann; French, Paul; Morrison, Anthony; Tai, Sara
Abstract: Clinicians are often sceptical about offering cognitive behavioural therapy (CBT) to individuals experiencing thought disorder. This view may result from perceived difficulties in clients being able to learn and better understand their experiences through verbal dialogue. However, it may also partly be due to the lack of clear guidance on how to address and work with these difficulties within therapy. This paper provides recommendations for delivering CBT in individuals experiencing thought disorder. It considers how clinicians might conduct their cognitive behavioural assessment, formulation, and intervention, targeting unhelpful appraisals and behaviour, and generating insight. The aim is to better disseminate the techniques sometimes applied in clinical practice.